2011
DOI: 10.1186/1471-2458-11-52
|View full text |Cite
|
Sign up to set email alerts
|

Trends in all cause and viral liver disease-related hospitalizations in people with hepatitis B or C: a population-based linkage study

Abstract: BackgroundPrevious studies have reported an excess burden of cancer and mortality in populations with chronic hepatitis B (HBV) or C (HCV), but there are limited data comparing hospitalization rates. In this study, we compared hospitalization rates for all causes and viral liver disease in people notified with HBV or HCV in New South Wales (NSW), Australia.MethodsHBV and HCV notifications were linked to their hospital (July 2000-June 2006), HIV and death records. Standardized hospitalization ratios (SHRs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…The contrasting trends in non-HCC liver-related mortality in our study are consistent with findings from a recent linkage study examining hospitalisations in New South Wales [40], which found a significant decrease in hospitalisation rates for non-alcoholic liver disease between 2000 and 2006 for both HBV and HCV infected people. The more striking trends in hospitalisation data are potentially explained by the relatively recent advances in antiviral treatment and uptake having impacted hospitalisation rates more immediately than mortality rates.…”
Section: Discussionsupporting
confidence: 91%
“…The contrasting trends in non-HCC liver-related mortality in our study are consistent with findings from a recent linkage study examining hospitalisations in New South Wales [40], which found a significant decrease in hospitalisation rates for non-alcoholic liver disease between 2000 and 2006 for both HBV and HCV infected people. The more striking trends in hospitalisation data are potentially explained by the relatively recent advances in antiviral treatment and uptake having impacted hospitalisation rates more immediately than mortality rates.…”
Section: Discussionsupporting
confidence: 91%
“…The current study indicated that the number of individuals with HCV‐related advanced liver disease and requiring liver transplantation has increased markedly during the last decade. These findings are in line with other Australian data demonstrating the increased liver‐related hospitalization and mortality among individuals with HCV infection . This rising burden of HCV‐related liver disease relates to the “ageing cohort” effect in the HCV infected population, low HCV treatment uptake, and sub‐optimal efficacy of interferon‐based treatments, particularly in advanced liver disease.…”
Section: Discussionsupporting
confidence: 89%
“…Liver disease already accounts for the greatest burden in hospital admissions among older HCV mono‐infected adults in New South Wales . In addition, hospital admissions for HCV‐related liver morbidity have recently increased . A marked increase in HCV treatment uptake will be required to reduce the incidence of advanced liver disease complications and deaths.…”
Section: Discussionmentioning
confidence: 99%